Business Ethics and Legal Protection Roles in Corporate Governance: A Case Study on Consumer Dispute Resolution in the Financial and E-Commerce Sectors - Hidayat, Dafit; Satory, Agus (Jurnal Locus Penelitian dan Pengabdian, 2025)
Globalization and digital technology development have brought significant changes to Indonesia’s financial services and e-commerce sectors. While these sectors offer major economic opportunities, they also pose serious challenges related to consumer protection. This study aims to analyze the role of business ethics and legal protection in corporate governance, particularly through a case study of consumer dispute resolution in financial services and e-commerce. The analysis focuses on the effectiveness of legal instruments such as the Consumer Protection Law (UUPK) and the Financial Services Authority (OJK) regulations, as well as dispute resolution mechanisms, both litigation and non-litigation, including the Consumer Dispute Resolution Agency (BPSK), Alternative Dispute Resolution Institutions (LAPS), and Online Dispute Resolution (ODR). The findings show that although the regulatory framework is normatively adequate, its effectiveness remains hindered by weak digital literacy among consumers, limited socialization, and the capacity of supervisory institutions. Consumers tend to prefer non-litigation pathways due to their faster, cheaper, and more flexible processes; however, the success of these mechanisms strongly depends on institutional independence, process transparency, and coordination with companies’ internal complaint systems. This study highlights that the implementation of business ethics based on transparency and fairness, combined with effective legal protection, is crucial in building consumer trust, enhancing corporate accountability, and supporting sustainable economic growth in the digital era.